Effects of alternative protein sources from food industry byproducts in starter feeds on dairy calf growth performance under different conditions: a preliminary study - Dosmukhamed Muratov; Bakhyt Kubekova; Madina Khassanova; Madina Smailova; Doskali Naimanov; Jan Miciński; Natalya Papusha (Frontiers in Animal Science)
IntroductionThis study evaluated the effects of alternative protein sources from food industry byproducts in starter feeds on dairy calf growth and metabolism under different feeding conditions.MethodsSixty Holstein × Black-and-White female calves were allocated into six groups across two commercial farms. Farm 1 included T1 (Starter A: 15% egg powder), T2 (Starter B: 15% feed yeast), and CON1 (standard starter); Farm 2 included T3, T4 (identical to T1 and T2, respectively), and CON2 (standard starter). All groups were monitored over a 90-day period for feed intake, weight gain, feed conversion ratio (FCR), and blood biochemical parameters. Starters also included milk whey and Bacillus subtilis as a probiotic. Statistical analyses were performed using ANOVA (P ≤ 0.05 considered significant).ResultsAt Farm 1, calves in group T2 demonstrated significantly greater weight gain (+3.47%, P = 0.01) and improved FCR (P = 0.03) compared to the CON1 group. Additionally, T2 calves showed elevated total protein (P = 0.04) and alkaline phosphatase (ALP) activity (P < 0.05), suggesting enhanced metabolic efficiency. At Farm 2, while growth and FCR differences were not statistically significant (P > 0.05), calves in T3 showed increased total protein at day 60 (P = 0.04) and elevated gamma-glutamyl transferase (GGT) at day 30 (P = 0.02).DiscussionThese preliminary findings suggest that incorporating food industry byproducts in starter feeds may improve feed efficiency and metabolic parameters in dairy calves. However, their effectiveness appears to depend on feeding conditions, including basal diet composition and feed palatability. Further investigation is needed to clarify these interactions and assess long-term effects.